Volatile volatility: Conceptual and measurement issues related to price trends and volatility - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2016)
In the 1990s, policy debates focused on global price levels and whether they were too low. Two recent food price spikes, in 2008 and 2011, have led to renewed concerns about the impact of high prices and shifted the focus back to food price volatility. The effects of changes in price trends on food production and food consumption (a discussion about price levels) are different from the effects of volatility changes around those trends (cycles and extreme events), but the two issues are related. This paper argues that analysis of these developments may benefit from differentiating between trends, cycles, and shorter-term events, including spikes and busts. After expanding on several methodological and data issues related to how these concepts are defined and measured, the paper concludes that although the price shocks of 2008 and 2011 focused the attention of the public and policymakers on price volatility, the decomposition of trends, cycles, and shorter-term volatility also suggests the need to find out whether price variations are responding to cyclical and shorter-term movements, or whether they are the result of a changing trend reflecting adjustments in long-term fundamentals that need to be properly understood.